Negative hepatic computed tomographic attenuation pattern in a dog with vacuolar hepatopathy and hepatic fat accumulation secondary to cushing's syndrome. Issue 5 (9th October 2017) - Carloni, Andrea; Paninarova, Michaela; Cavina, Damiano; Romanucci, Mariarita; Salda, Leonardo Della; Teodori, Simone; Vignoli, Massimo
Abstract: This report describes an unusual computed tomographic (CT) hepatic pattern, characterized by negative attenuation values (from –19.59 to –28.85 Hounsfield Units, HU) in a canine patient with severe Cushing's syndrome. Attenuation values of the splenic parenchyma (63.26 HU) and abdominal fat (–118.34 HU) were within normal limits. The negative hepatic attenuation values allowed a CT diagnosis of severe hepatic fatty infiltration that was subsequently confirmed by tissue‐core biopsy and histopathological examination.